Distribution shifts of freshwater fish under a variable climate: comparing climatic, bioclimatic and biotic velocities. Issue 9 (14th July 2015) - Comte, Lise; Grenouillet, Gaël; Heikkinen, Risto
Abstract Aim We aimed to quantify how stream fish species have responded to short‐term variability in climate across eight consecutive periods over the last 20 years by comparing biotic (velocities of observed species range shifts) to expected bioclimatic (velocities of climate‐induced shift in the suitable habitat of species) velocities, a measure combining species‐specific exposure and sensitivity to climate. Location French streams. Methods Occupancy models were developed to model the distribution of 14 species across eight consecutive time periods between 1992 and 2011 and to project climate‐induced changes in the distribution of suitable area over time. Based on the projected changes in habitat suitability, we first estimated the bioclimatic velocities for each species and each transition between consecutive periods. We then applied the same approach to the observed changes in suitable habitat to estimate the observed biotic velocities. Finally, the velocities of range shifts were compared to those expected on the basis of climate changes for each reach of the hydrographic network and the consistency of distributional responses – and potential lags – across species and transitions were quantified. Results We found that biotic velocities were overall consistent with expectations, with observed responses matching both the direction and magnitude of bioclimatic velocities. Nonetheless, we also show that species consistently lagged behind climate (mean = 4.64 m.year−1). Lags in habitat gain were more pronounced than those in habitat loss and revealed differential vulnerability of local populations within species distributions. Main conclusions These findings demonstrate that integrating species‐specific sensitivities to climate into measures of climatic velocities (namely bioclimatic velocities) provide improved expectations for observed range shifts. They also suggest that stream fish may display both low ability to persist under short periods of unfavourable climate and limited capacity to disperse upstream towards newly suitable habitats.